Mapping the citation network on vitamin D research in Australia: a data-driven approach - Neo, Belinda; Qu, Xiaochen; Dunlop, Eleanor; Shepherd, Carrington; Walsh, Erin I.; Cherbuin, Nicolas; Black, Lucinda J. (Frontiers in Medicine, 2023)
Vitamin D research can vary geographically, as vitamin D status is influenced by latitude, season, dietary intake, body mass index, ethnicity, and public health initiatives. Over the last two decades, research on vitamin D has increased in Australia, where the potential for sun exposure (a major source of vitamin D) is high. We aimed to identify key topics and gaps in vitamin D research in Australia using a data-driven approach. A literature search limited to Australian studies was conducted in the Web of Science Core Collection database. Citation network analysis was conducted to identify clusters and sub-clusters, depicted using word clouds. Topic analysis of each cluster and sub-cluster was conducted to identify topics and sub-topics, respectively. From 934 publications (over the period 1984 -2022), nine topics and 60 sub-topics were identified. The nine topics were: vitamin D in vulnerable populations and its impact on child development; the impact of sun exposure and ultraviolet-B radiation on various health conditions; vitamin D and falls and fractures in older adults; vitamin D and its association with health outcomes; vitamin D from sun exposure; testing of vitamin D status in Australia; vitamin D, calcium, and musculoskeletal health; vitamin D status and knee osteoarthritis; and vitamin D status and exercise performance in athletes. There were limited publications on vitamin D in Aboriginal and Torres Strait Islander peoples and dietary vitamin D. We have provided an overview of vitamin D research in Australia. The research trends and knowledge gaps identified can guide future research to better inform public health initiatives in Australia.